Energy efficiency of diabatic distillation schemes for an acetone–toluene–n-butanol mixture with an entrainer in the first column - P. S. Klauzner; D. G. Rudakov; E. A. Anokhina; A. V. Timoshenko (Тонкие химические технологии, 2023)
Objectives. To investigate the effectiveness of various options for organizing the process of diabatic distillation in the separation of a mixture of acetone–toluene–n-butanol by extractive distillation (ED) with dimethylformamide as an entrainer in a scheme where an entrainer is used in the first column.Methods. Mathematical modeling in the Aspen Plus v. 12.1 software package was used as the primary research method. The local Non-Random Two Liquid composition equation was used as a model for describing vapor–liquid equilibrium. Parametric optimization of diabatic schemes was carried out according to the criterion of reduced energy costs.Results. Based on ED scheme for an acetone–toluene–n-butanol mixture with an entrainer in the first column, four options for organizing diabatic distillation schemes were considered, both with and without increasing the temperature of the flows due to compression.Conclusion. It is shown that the use of diabatic schemes in the ED of an acetone–toluene–n-butanol mixture with dimethylformamide can decrease energy consumption by 11–17%. While the maximum reduction in energy consumption is achieved in a scheme using a compressor, the efficiency of schemes without a compressor is slightly lower. Nevertheless, the technological design of the latter is much simpler.